2018
DOI: 10.1021/acs.macromol.8b01786
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement on Alternating Copolymerization of Carbon Monoxide and Styrene by Dibenzobarrelene-Based α-Diimine Palladium Catalysts

Abstract: CO/styrene copolymerization by α-diimine palladium catalysts is a promising method for direct synthesis of polyketones. The effect of the catalyst backbone structure on CO/styrene copolymerization has been studied with the aim of developing robust α-diimine palladium catalysts able to improve the polymerization productivity and controllability. Dibenzobarrelene derived α-diimine palladium catalysts without o-aryl substituents were designed and synthesized for CO/styrene alternating copolymerization. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 68 publications
1
51
0
Order By: Relevance
“…Three-dimensional geometry Ni-and Pd-based α-diimine complexes with a bulky bridged backbone. [105][106][107][108][109][110][111] played high thermal stability, high activities of up to 3.2 × 10 6 g PE (mol Pd h) −1 (60°C, 15 min), and high polymer M n (up to 538 000) in ethylene polymerization. More interestingly, semicrystalline low-density branched (23-29/1000 C) PEs with high T m of up to 99°C were obtained.…”
Section: Fig 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional geometry Ni-and Pd-based α-diimine complexes with a bulky bridged backbone. [105][106][107][108][109][110][111] played high thermal stability, high activities of up to 3.2 × 10 6 g PE (mol Pd h) −1 (60°C, 15 min), and high polymer M n (up to 538 000) in ethylene polymerization. More interestingly, semicrystalline low-density branched (23-29/1000 C) PEs with high T m of up to 99°C were obtained.…”
Section: Fig 17mentioning
confidence: 99%
“…17) bearing a dibenzobarrelene backbone. [105][106][107][108] The precision synthesis of functionalized polyolefins was achieved by Pdcatalyzed living coordination copolymerization of ethylene with various acrylate comonomers. 105 In this system, the molecular weight, polydispersity, composition and branching topology of the E/MA copolymers can be tuned by changing ethylene pressure.…”
Section: Modifications Of the α-Diimine Backbone Structuresmentioning
confidence: 99%
“…[ 37 ] The low solubility of the polymers, which are only soluble in HFIP, may be related to their high syndiotacticity. [ 13 ]…”
Section: Resultsmentioning
confidence: 99%
“…Such [Pd (bdompp(Y) 2 )] complexes have been employed in commercial processes to produce “Carilon.” [ 1,5–8 ] Carilon is the first commercial polyketone derived from CO and olefins by [Pd (bdompp(Y) 2 )] catalysts. N‐N ligands exhibit greater catalytic activities than P‐P ligands for the copolymerization of vinyl arene and CO. [ 9–17 ] Moreover, N‐N ligands such as bipyridine, phenanthroline, and pyridine‐imidazoline are also employed for the terpolymerization of CO, vinyl arene, and ethylene (Figure 1). [ 18–20 ] While a variety of ligand‐modified palladium catalysts are used to polymerize various olefins and CO, direct comparisons of the catalytic activities among catalyst systems for the copolymerization and terpolymerization of ethylene, vinyl arenes, and CO has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the specific high-temperature decomposition mechanism for late-transition metal catalysts is still unclear, yet one widely accepted explanation ascribes it to the C-H activation that occurs between the metal center and alkyl groups located on the ortho-position of the N -aryl fragment after it rotates to the coordination plane [ 16 ]. Therefore, suppressing N -aryl rotations is believed to be one of the most efficient strategies to enhance the thermal stability of these complexes, and in the past few years, various intra-ligand covalent and non-covalent interactions, e.g., hydrogen bonding, π,π-stacking, etc., have been introduced to ligand design, aiming to fasten the N -aryl moiety and to subsequently prohibit its rotation [ 17 , 18 , 19 ]. In the present research, ortho-substituted dibenzhydryl groups were introduced to the N -aryl moiety of α -diimine cobalt complexes, and surprisingly, it was found that one of the aryl groups in dibenzhydryl could form π,π-interaction with the acenaphthenyl backbone, which subsequently endows the complexes with excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%